Stable carbon isotope ratios of ambient aromatic volatile organic compounds - A. Kornilova; L. Huang; M. Saccon; J. Rudolph (Atmospheric Chemistry and Physics, 2016)
Measurements of mixing ratios and stable carbon isotope ratios of aromatic volatile organic compounds (VOC) in the atmosphere were made in Toronto (Canada) in 2009 and 2010. Consistent with the kinetic isotope effect for reactions of aromatic VOC with the OH radical the observed stable carbon isotope ratios are on average significantly heavier than the isotope ratios of their emissions. The change of carbon isotope ratio between emission and observation is used to determine the extent of photochemical processing (photochemical age, ∫ [OH]dt) of the different VOC. It is found that ∫ [OH]dt of different VOC depends strongly on the VOC reactivity. This demonstrates that for this set of observations the assumption of a uniform ∫ [OH]dt for VOC with different reactivity is not justified and that the observed values for ∫ [OH]dt are the result of mixing of VOC from air masses with different values for ∫ [OH]dt. Based on comparison between carbon isotope ratios and VOC concentration ratios it is also found that the varying influence of sources with different VOC emission ratios has a larger impact on VOC concentration ratios than photochemical processing. It is concluded that for this data set the use of VOC concentration ratios to determine ∫ [OH]dt would result in values for ∫ [OH]dt inconsistent with carbon isotope ratios and that the concept of a uniform ∫ [OH]dt for an air mass has to be replaced by the concept of individual values of an average ∫ [OH]dt for VOC with different reactivity.